PUTUSAN PEMIDANAAN BAGI TERDAKWA AKIBAT DITUNTUT BALIK OLEH TERLAPOR YANG DIJATUHI PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM - Retno Hernani (Dinamika, 2021)
The sentence to escape from all lawsuits as regulated in Article 191 paragraph (2) of the Criminal Procedure Code, in its application in court, not all judges apply Article 191 paragraph (2) of the Criminal Procedure Code in issuing sentencing decisions against the defendant in case Number 1394/Pid.B/2019/ PN Sby, as a result of being prosecuted back by someone who has been criminally reported and has been sentenced to escape from all lawsuits in case Number 2570/Pid.B/2016/PN Sby.This study uses a statute approach and a case approach. The processing of legal materials obtained in the literature study and document study were analyzed normatively using interpretation/interpretation so that analysis could be carried out and answers to problems were obtained to draw conclusions.Keywords: Criminal Sentence, Sentence to Release from All Lawsuits